The Role of Local Governments in the Transformation of Public Spaces: The Case of Atakum City Square - Deniz YILDIZ USLU; Tuğçe ŞANLI KATI (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2025)
Beyond being physical spaces, public spaces are critical for social interaction and social integration. Local governments have great influence over public spaces due to their authority to regulate, improve and open these spaces for use. Power conflicts between local governments and plan changes accelerate the transformation of these spaces. This article examines the effects of interventions and power dynamics in planning processes on the transformation of public spaces through the example of Atakum City Square. It presents a theoretical framework for public spaces and squares and evaluates how planning decisions and local government actions affect the functionality and social dynamics of public spaces. In the study, qualitative and quantitative methods are combined to collect data through spatial observations, interviews with local government representatives and user surveys. The main findings show that the power dynamics of local governments affect the functional structure of the square and lead to a narrowing of the diversity of activities. Despite physical improvements, social inclusion deficiencies persist. This study contributes to the literature by providing recommendations for the preservation of democratic and inclusive public spaces.